Buying Supermajorities in the Lab - Sebastian Fehrler; Maik T. Schneider (Institute of Labor Economics (IZA), 2019)
Many decisions taken in legislatures or committees are subject to lobbying efforts. A seminal contribution to the literature on vote-buying is the legislative lobbying model pioneered by Groseclose and Snyder (1996), which predicts that lobbies will optimally form supermajorities in many cases. Providing the first empirical assessment of this prominent model, we test its central predictions in the laboratory. While the model assumes sequential moves, we relax this assumption in additional treatments with simultaneous moves. We find that lobbies buy supermajorities as predicted by the theory. Our results also provide supporting evidence for most comparative statics predictions of the legislative lobbying model with respect to lobbies' willingness to pay and legislators' preferences. Most of these results carry over to the simultaneous-move set-up but the predictive power of the model declines.
Keywords: C92; D72; 330; legislative lobbying; vote-buying; Colonel Blotto; multi-battlefield contests; experimental political economy